2010
DOI: 10.4103/0256-4947.65259
|View full text |Cite
|
Sign up to set email alerts
|

Fever of unknown origin: 98 cases from Saudi Arabia

Abstract: BACKGROUND AND OBJECTIVES:Fever of unknown origin (FUO) is mainly secondary to infectious, neoplastic or inflammatory diseases. To increase the body of knowledge on this diagnosis in the region, we collected information on all patients admitted to our institution with FUO in a 13-year period.METHODS:We conducted a retrospective chart review of all immunocompetent males and females aged 13 years and older admitted between January 1995 and June 2008 who fulfilled the criteria for FUO. Data collection included de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 19 publications
1
10
0
Order By: Relevance
“…Among them, tuberculosis remains an important cause of FUO. In a study conducted in Pakistan, most of the infectious cases were pulmonary TB (22) but most researchers in our region found that extrapulmonary TB was more common than pulmonary TB (8,16,23,24). In our series, tuberculosis constituted 27.7% of the infectious cases.…”
Section: Discussionmentioning
confidence: 46%
See 1 more Smart Citation
“…Among them, tuberculosis remains an important cause of FUO. In a study conducted in Pakistan, most of the infectious cases were pulmonary TB (22) but most researchers in our region found that extrapulmonary TB was more common than pulmonary TB (8,16,23,24). In our series, tuberculosis constituted 27.7% of the infectious cases.…”
Section: Discussionmentioning
confidence: 46%
“…This rheumatologic disease has also been reported as the most common noninfectious inflammatory cause of FUO in other studies in our region (28,30). On the other hand, some researchers have found systemic lupus erythematosus as the most common connective tissue disease among FUO cases (16,22,24,26). Other connective tissue diseases as the causes of fever in our FUO cases were undifferentiated polyarthritis, rheumatoid arthritis, systemic lupus erythematosus, giant cell arteritis, Wegener's granulomatosis, Behcet's diseases, and bullous pemphigoid, each of which was found in one patient.…”
Section: Discussionmentioning
confidence: 99%
“…More than 200 causes of FUO have been reported [ 4 ] and inflammatory bowel disease is among them [ 3 , 9 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Phase 1 diagnostic protocol is adopted in patients without potential diagnostic clues (PDCs) or with misleading clues, and a phase 2 diagnostic protocol for patients without PDCs is applied when phase 1 did not reveal any. In Saudi Arabia [22], a single diagnostic work-up is done for all cases of FUO that involve most of the abovementioned investigations. This variability in diagnostic work-up shows the lack of unified approach and guidelines to handle the cases of FUO.…”
Section: Discussionmentioning
confidence: 99%